2006
DOI: 10.1055/s-2006-949655
|View full text |Cite
|
Sign up to set email alerts
|

Starting Insulin Therapy in Type 2 Diabetes: Twice-Daily Biphasic Insulin Aspart 30 Plus Metformin versus Once-Daily Insulin Glargine Plus Glimepiride

Abstract: Starting insulin in Type 2 diabetes patients with twice-daily BIAsp 30 plus met can reduce HbA (1c) and mean prandial plasma glucose increment to a greater extent than once-daily glarg plus glim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 14 publications
(21 reference statements)
12
110
0
2
Order By: Relevance
“…As a result of the improved glycemic control, 64.5% patients in subject‐driven group met the HbA 1c target. Effective glycemic control was also reported in other trials where dose adjustment of BIAsp 30 BID was self‐decided by patients13, 14, 15, 16. The reduction of HbA 1c was 1.4–2.5% in those trials, which was similar to that reported in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…As a result of the improved glycemic control, 64.5% patients in subject‐driven group met the HbA 1c target. Effective glycemic control was also reported in other trials where dose adjustment of BIAsp 30 BID was self‐decided by patients13, 14, 15, 16. The reduction of HbA 1c was 1.4–2.5% in those trials, which was similar to that reported in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…102 Other studies have documented weight increases or weight stasis after treatment with glargine, although the weight increases, when observed, tended to be less than those occurring with NPH insulin. [103][104][105][106][107][108][109][110][111][112][113][114] The mechanisms behind the weight-sparing trait of insulin detemir have yet to be fully clarified. Insulin detemir is associated with a lower risk of hypoglycemia relative to other basal insulin preparations, 99,108,115 consistent with its greater pharmacokinetic predictability and smooth time-action profile.…”
Section: Weight Gainmentioning
confidence: 99%
“…The present study showed that exenatide + MET combination therapy was superior to BIA30 + MET combination therapy for the treatment of overweight or obese patients newly diagnosed with T2DM. It should be taken into account that in the present study, all patients were treated with a combination therapy, whereas only one report demonstrated that a double combination was beneficial for the therapy of T2DM patients (20); however, since the double and combination therapies involve subcutaneous injections of the agents at the same time twice daily and have the potential to favorably affect fasting and post-prandial glucose, they may be considered to be suitable interventions. Exenatide has been shown to improve glycemic control in patients with T2DM who failed to achieve glycemic control with maximally effective MET doses (29).…”
Section: Discussionmentioning
confidence: 88%
“…However, the effectiveness of the combination remains to be elucidated in overweight or obese patients with newly diagnosed type 2 diabetes mellitus. MET and BIA30 may reduce HbA (1c) and mean prandial plasma glucose increment to a greater extent in diabetic patients when compared with the patients treated with insulin glargine plus glimepiride (20). To the best of our knowledge, the efficacy of a combination therapy of MET and BIA30 has not yet been reported in specifically obese patients, only in general diabetic patients, and the efficacy and safety of the two combination therapies (exenatide or BIA30 and MET) in treating T2DM have not been previously compared, which was the purpose of the present study.…”
Section: Introductionmentioning
confidence: 98%